Prevalence and Associated Factors of Thinness among School-Aged Children in Public and Private Primary Schools in Kandahar City: A Comparative Study - Tareen, Zarghoon; Sharma, Sandesh Kumar; Farooqi, Khushhal; Tareen, Ahmad Tameem; Rafiqi, Najibullah (International Journal of Child Health and Nutrition, 2026)
Background: Thinness, which is a marker of acute undernutrition, is a major public health problem among school-aged children in developing countries. For Afghanistan, little information exists on the prevalence and factors associated with thinness among school-aged children in public and private schools. Objective: To find out the prevalence of thinness and its associated factors among school-aged children in public and private primary schools of Kandahar City, Afghanistan. Methods: The analytical cross-sectional study was carried out in schools from May to December 2025 among 885 children aged 6-12 years. The participants were selected by multistage random sampling from 10 public and 10 private schools. Data was collected by pre-testing a questionnaire and standardized anthropometric techniques. Thinness was measured by the WHO Anthro Plus software. Binary logistic regression was performed to identify factors independently associated with thinness, with significance at p < 0.05. Results: The prevalence of thinness was 8.1% in general. The prevalence of thinness was higher in public than in private schools (11.1% vs. 5.2%) and higher among girls than among boys (10.2% vs. 6.1%). Using multivariate analysis, factors independently associated with thinness were low household income (AOR: 2.75), low dietary diversity (AOR: 4.24), diarrheal illness in the past two weeks (AOR: 3.92), and polygamy (AOR: 3.10). Conclusion: Thinness is currently a significant issue among school-aged children in the city of Kandahar. There is a need for interprofessional interventions across nutrition, health, and social protection to address children’s nutritional problems.